Effects of storage solutions on mineral contents of dentin - Asli Secilmis; Erhan Dilber; Fatma Gokmen; Nilgun Ozturk; Tuba Telatar (Elsevier, 2011)
Background/purpose: It is important to understand how storage conditions affect the tooth structure for in vitro studies. There is little information regarding the selection of an appropriate storage solution. This study was conducted to determine the influence of storage solutions on the mineral contents of dentin. Materials and methods: Ninety dentin specimens were obtained from 30 molar teeth. Specimens were divided into two groups of 45 each (storage for 45 and 90 days). Each of the two groups was further divided into nine storage solution groups (n=5). For the control group, freezing was used to store the teeth. The mean percentage weights of calcium, potassium, sodium, and phosphorus in each dentin slab were measured by inductively coupled plasma-atomic emission spectrometry. Two-way analysis of variance and Tukey's honest significant difference test were used to analyze the data (P=0.05). Results: There were significant differences in calcium among groups. The potassium level of slabs stored in artificial saliva and the sodium level of slabs stored in buffered solutions and saline solution increased (P<0.05). Potassium, sodium, and phosphorus levels were highest when stored for 45 days (P<0.05). Conclusion: The storage solution and storage time affected the compositional structure of dentin. The results suggest that storage processes may influence outcomes of in vitro dental research.